An Empirical Study on the Risk Diversification Effect in the Share Market in the Post-Pandemic Era - Luo, Penglan (Exploring Science Academic Conference Series, 2026)
This study investigates the efficacy of traditional diversification strategies within the Chinese A-share market during the post-pandemic era (2023–2025). Contrary to the stable correlation structures assumed by Modern Portfolio Theory, empirical analysis of 30–50 liquid stocks reveal a structural shift in market dynamics. While the results confirm that diversification statistically reduces portfolio volatility, the magnitude of risk reduction is significantly weaker than theoretical predictions, with portfolio standard deviation only 35% lower than individual stock volatility. This diminished effect is attributed to a pronounced increase in cross-sector correlations—exemplified by technology and healthcare correlations exceeding 0.60—driven by systemic shocks and herding behavior. The findings suggest that historical covariance data may no longer reliably predict risk reduction, necessitating adaptive asset allocation strategies in the face of persistent macroeconomic uncertainties.